2004
DOI: 10.1093/hmg/ddi014
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional dysregulation in striatal projection- and interneurons in a mouse model of Huntington's disease: neuronal selectivity and potential neuroprotective role of HAP1

Abstract: Transcriptional dysregulation has been described as a central mechanism in the pathogenesis of Huntington's disease (HD), in which medium spiny projection neurons (MSN) selectively degenerate whereas neuronal nitric-oxide-synthase-positive interneurons (nNOS-IN) survive. In order to begin to understand this differential vulnerability we compared mRNA levels of selected genes involved in N-methyl-D-aspartate (NMDA) glutamate receptor and calcium (Ca2+) signaling pathways in MSN and nNOS-IN from 12-week-old R6/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 75 publications
4
83
1
1
Order By: Relevance
“…These mice, and in particular the R6/2 line, have an early onset of symptoms and a fast progression of the disease, showing a life expectancy of approximately 12 to 17 weeks, depending on the colony. The phenotype and neuropathology observed in these mice replicate several features observed in humans, including a progressive motor Luesse et al, 2001;Bolivar et al, 2003Bolivar et al, , 2004 and cognitive impairment Murphy et al, 2000), weight loss, decreased striatal and brain size (Mangiarini et al, 1996), ubiquitinated nuclear and cytoplasmic inclusions of the mutant protein (Davies et al, 1997;Li et al, 1999), altered levels of neurotransmitters (for review see Cha, 2000) and their receptors (Cha et al, 1998), altered gene expression (Luthi-Carter et al, 2000Zucker et al, 2005), diabetes (Hurlbert et al, 1999;Luesse et al, 2001;Andreassen et al, 2002;Björkqvist et al, 2005), which was previously reported in 10-25% of HD patients (Podolsky et al, 1972;Farrer, 1985), as well as several other neuroendocrine changes for review see Petersén and Björkqvist, 2006), and premature death (Mangiarini et al, 1996). Interestingly, both R6/2 (Gil et al, 2004 and R6/1 (Lazic et al, 2004(Lazic et al, , 2006 mice show a specific decrease in hippocampal cell proliferation and neurogenesis, which may account for some of their cognitive deficits (see below).…”
Section: Introduction -The R6 Micesupporting
confidence: 56%
“…These mice, and in particular the R6/2 line, have an early onset of symptoms and a fast progression of the disease, showing a life expectancy of approximately 12 to 17 weeks, depending on the colony. The phenotype and neuropathology observed in these mice replicate several features observed in humans, including a progressive motor Luesse et al, 2001;Bolivar et al, 2003Bolivar et al, , 2004 and cognitive impairment Murphy et al, 2000), weight loss, decreased striatal and brain size (Mangiarini et al, 1996), ubiquitinated nuclear and cytoplasmic inclusions of the mutant protein (Davies et al, 1997;Li et al, 1999), altered levels of neurotransmitters (for review see Cha, 2000) and their receptors (Cha et al, 1998), altered gene expression (Luthi-Carter et al, 2000Zucker et al, 2005), diabetes (Hurlbert et al, 1999;Luesse et al, 2001;Andreassen et al, 2002;Björkqvist et al, 2005), which was previously reported in 10-25% of HD patients (Podolsky et al, 1972;Farrer, 1985), as well as several other neuroendocrine changes for review see Petersén and Björkqvist, 2006), and premature death (Mangiarini et al, 1996). Interestingly, both R6/2 (Gil et al, 2004 and R6/1 (Lazic et al, 2004(Lazic et al, , 2006 mice show a specific decrease in hippocampal cell proliferation and neurogenesis, which may account for some of their cognitive deficits (see below).…”
Section: Introduction -The R6 Micesupporting
confidence: 56%
“…If mutant htt can alter the activity of p53, one would predict that cells expressing mutant htt might have numerous changes in their transcriptional profile. In fact, a number of transcriptional alterations have been identified by gene expression profile, RT-PCR, and Northern blot in response to mutant htt (Li et al, 1999;Cha, 2000;Luthi-Carter et al, 2000;Luthi-Carter et al, 2002;Sipione et al, 2002;Kotliarova et al, 2005;Zucker et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that nNOS is restricted to occasional interneurons in the hippocampus (Dinerman et al, 1994). In the mouse striatum, furthermore, nNOS-positive cells are known to be interneurons (Zucker et al, 2005). However, little is known about the exact changes of nNOS expression as interneurons in the hippocampus after transient cerebral ischemia in gerbils.…”
Section: Discussionmentioning
confidence: 99%